Studi Analisis Potensi Penghematan Konsumsi Energi Melalui Audit Dan Konservasi Energi Listrik Di Rumah Sakit Universitas Riau - Medio Saputra; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The cost of electrical bill in most of hospital in this big cities indicates getting high. This phenomenal can be anticipated through auditing. By doing this audit will be able to determine the cost factor and the related issue. This paper purposes audit energy to a hospital to evaluate the potential energy saving to reduce wastes of energy for unnecessary things. In this analysis will be obtained the hospital operational cost in the efficient way. The raw data is findout by observation and direct measurement in the respective hospital. The measurement of power quality in the electricity panel main by using the instrumention of power quality analyzer (PQA). The output of this instrumen has managed to figure out the following parameters i.e. output of voltage (V) , the current (ampere) , power factor (cosphi) , active power (W) , power reactive (VAR) and power imaginery (VA). Base on the measuremant result, the power quality status the hospital is obtained. In the overall, the following results are describing i.e. energy consumtion intensity (ECI) is 6,1 kWh/m2/month for non ac room and considered as inefficient criteria and 12,89 kWh/m2/month for ac room considered as efficient criteria .The measurement also to include the lighting component to get the intensity of light to compare the condition a standard value. For lighting in health the department of health, the Republic of Indonesia .This is to be increased consideration lighting done in order to meet standards , with the type of Fluorescent Lamp with light LED(Light Emitting Diode)Keywords: audit energy, quality energy, standards, compare, power quality analyzer (PQA)